Diferensiasi Produk Pada Usaha Pengrajin Kerupuk Aneka Buah, Sayur, Dan Rasa M. Satuwin Krembung sidoarjo - Riza, Denny Ainur; Pinando, Sugeng (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Basically, the success of a company in the manufacturing and marketing their products, is determined by the accuracy of methods used by the company is implementing policies that product differentiation is a business that is specific differentiation of various products produced. Craftsmen Enterprises Crackers M. Satuwin is a business that produces a variety of crackers, including a variety of fruit crackers, crackers mixed vegetables, crackers and a variety of flavors. However, the products supplied by Craftsmen Enterprises Crackers M. Satuwin not necessarily make prospective customers into buying the product settled crackers, crackers because there are similar products in the market, the product has less advantage, limited production, as well as the equipment used is still quite traditional and simple. Possible problems related to product differentiation such as: saturation product, product suitability, crackers are less diverse shapes, sizes crackers, and less attractive packaging. If possible the problem is not addressed, then it is likely to affect the number of customers, leading to consumer frustration, boredom consumers, consumers turn to competitors, the product less attractive, and the survival of the company affected. The purpose of this study was to determine the product differentiation is done (the current state and future) so that the product can be superior to competitors, businesses more widely known by the market, and the increasingly popular consumer products. Keywords :Â Product Differentiation, Craftsman Crackers, Assorted Fruit, Vegetable, and taste.